2019
DOI: 10.1002/jmv.25394
|View full text |Cite
|
Sign up to set email alerts
|

Association between miRNA‐146a rs2910164 (G/C) polymorphism with the susceptibility to chronic HBV infection and spontaneous viral clearance in an Iranian population

Abstract: Hepatitis B virus (HBV) infection is one of the clinical dilemmas in chronic liver diseases. MicroRNAs (miRNAs) are small noncoding RNA molecules that play an important role in the pathogenesis of liver diseases and single nucleotide polymorphisms (SNPs) in miRNA genes affect the clinical course of HBV infection. Previous studies have shown that miRNA‐146a rs2910164 polymorphism can be associated with the pathogenesis of liver diseases such as hepatocellular carcinoma. The present study investigated the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…(D) Quantification from C. The two-independent t-test was used to compare the difference of wound healing rate and cell number. ÃÃ P < 0.01; ÃÃÃ P < 0.001. to HBV infection and with spontaneous viral clearance (Khanizadeh et al, 2019). TP53 mutation, the most common mutation in HCC, affects the progression and prognosis of HCC (Long et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(D) Quantification from C. The two-independent t-test was used to compare the difference of wound healing rate and cell number. ÃÃ P < 0.01; ÃÃÃ P < 0.001. to HBV infection and with spontaneous viral clearance (Khanizadeh et al, 2019). TP53 mutation, the most common mutation in HCC, affects the progression and prognosis of HCC (Long et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…1 , after precluding 193 irrelevant studies as judged from their titles and/or abstracts, the remaining 36 articles were reviewed for a more detailed evaluation. Based on the exclusion criteria, 7 studies were excluded: 1 about a review ( 25 ), 3 for insufficient data to evaluate OR and 95%CI ( 26 28 ), 2 for control group with HCC ( 29 , 30 ), and 1 for case group uncontained HCC( 31 ). Consequently, 29 studies met the inclusion criteria in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In China, the persistent exacerbation of HBV amplification is the main determinant of HCC recurrence (Yanming et al 2019). A recent study showed that miR-146a SNP (C/G) is associated with the susceptibility to HBV infection and with spontaneous viral clearance (Khanizadeh et al 2019). TP53 mutation, the most common mutation in HCC, affects the progression and prognosis of HCC (Long et al 2019).…”
Section: Discussionmentioning
confidence: 99%